2015
DOI: 10.1155/2015/597264
|View full text |Cite
|
Sign up to set email alerts
|

Natural Hirudin Increases Rat Flap Viability by Anti-Inflammation via PARs/p38/NF-κB Pathway

Abstract: The present study aimed to evaluate the effect of natural hirudin on rat random skin flap viability and to determine the mechanism. Forty-eight rats were randomly divided into 2 groups. After the dorsal skin flap operation (3 cm × 10 cm in size), subcutaneous injections of 6 ATU hirudin were administered to group H (n = 24) every 12 h, while group C (n = 24) received an equal volume of 0.9% normal saline. Six rats from each group were euthanized 1, 2, 4, and 7 days after the operation. A full skin sample was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Ischemic damage to the flap tissue and subsequent necrosis can be augmented by clinical and pharmacological interventions that suppress oxidative tissue damage or increase tissue tolerance against injury (3,4). There are several chains of molecular and cellular events which cause flap necrosis including the lack of the nutrients and ATP, oxidative stress, and inflammatory responses (5).…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic damage to the flap tissue and subsequent necrosis can be augmented by clinical and pharmacological interventions that suppress oxidative tissue damage or increase tissue tolerance against injury (3,4). There are several chains of molecular and cellular events which cause flap necrosis including the lack of the nutrients and ATP, oxidative stress, and inflammatory responses (5).…”
Section: Introductionmentioning
confidence: 99%
“…5 Based on this, a considerable amount of research has been done with the aim to increase tissue viability. [6][7][8][9][10][11][12] The evaluation of the results of interventions performed in experimental models of skin grafts and flaps include some methods, such as gene expression analysis, 10,13 protein expression analysis, 11,12,[14][15][16] assessment of histological changes, 11,12,15 and the percentage of viable tissue. 6,7,17,18 The latter is widely used for being fast, inexpensive, and efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Three methods can be used to evaluate the percentage of viable tissue: weight of paper template (WPT), 17,18 paper template area (PTA), 19 and photographic area (PA). 11,14,16 The paper template method was first described by Sasaki and Pang in 1980 20 and since then it has been used to evaluate the percentage of flap necrosis on the seventh postoperative day. This technique takes into consideration the weight of the template paper where the flap has been drawn to calculate its viability.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that ischemia-reperfusion can induce the production of cytokines, such as IL-1β, TNF-α in endothelial and inflammatory cells. Notably, the expression of inflammatory mediators and factors (such as IL-1, IL-6 and TNF-α) exacerbates the inflammatory response, while the inhibition of NF-κB expression prevents the release of inflammatory factors [ 22 – 23 ] . It is suggested that the activation of inflammatory signaling pathway participates in ischemia-reperfusion-induced injury of vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%